Efektivitas Penggunaan Dana Desa Di Desa Bukit Kecamatan Betung Kabupaten Banyuasin - Juniarsyah, Ivan; Lisdiana, Lisdiana; Mardianto, Mardianto (@-Publik: Jurnal Administrasi Publik, 2024)
Village Fund Management in Bukit Village, Betung District, Banyuasin Regency, is fully allocated for infrastructure improvements. However, there are problems in the effectiveness of managing these funds, namely the lack of transparency in the information provided by authorized officials to citizens, which causes this program to not be implemented effectively. This research is descriptive research with a qualitative approach. The theory used is the Effectiveness Measure Theory by Edy Sutrisno (2007:125-126), which includes the dimensions of Program Understanding, Right on Target, On Time, Achievement of Goals, and Real Change. The results of the research show that some uses of village funds are effective and some are not yet effective. In terms of Program Understanding, the level of understanding is classified as very low, which is caused by an educational background that requires further guidance and socialization regarding village fund management. Apart from that, coordination with the community of Bukit Village, Betung District, needs to be improved because miscommunication often occurs between work units, both within the village government itself, between the government and the community, as well as between the government and stakeholders in planning the development of village fund management in Bukit, District Betung, Banyuasin Regency.